The contribution of geography to the development of tourism research in Poland - Jackowski, Antoni (Turyzm/Tourism, 2011)
The article presents, both chronologically and thematically, the contribution of geography to the development of tourism research. The discussion concerns the situation in Poland but is presented in the context of the development of tourism geography in Europe and globally. The analysis includes only theoretical-methodological research. The output of Polish tourism geography after World War II has been considerable and comprises around 800 publications.